Inhibitory effects of Gymnema inodorum (Lour.) Decne leaf extracts and its triterpene saponin on carbohydrate digestion and intestinal glucose absorption - Wanwisa Srinuanchai (2022)
Ethnopharmacological relevance: Chiang-Da, Gymnema inodorum (Lour.) Decne. (GI), is an ethnomedicinal plant that has been used for diabetic treatment since ancient times. One of the anti-diabetic mechanisms is possibly related to the actions of triterpene glycoside, (3β, 16β)-16,28-dihydroxyolean-12-en-3-yl-O-β-D-glucopyranosyl-β-D-glucopyranosiduronic acid (GIA1) in decreasing carbohydrate digestive enzymes and intestinal glucose absorption in the gut system. Aims of the study: To observe the amount of GIA1 in GI leaf extracts obtained from different ethanol concentrations and to investigate the anti-hyperglycemic mechanisms of the extracts and GIA1. Materials and methods: The crude extracts were prepared using 50%v/v to 95%v/v ethanol solutions and used for GIA1 isolation. The anti-hyperglycemic models included in our study examined the inhibitory activities of α-amylase/α-glucosidase and intestinal glucose absorption related to sodium glucose cotransporter type 1 (SGLT1) using Caco-2 cells. Results: GIA1 was found about 8%w/w to 18%w/w in the GI extract depending on ethanol concentrations. The GI extracts and GIA1 showed less inhibitory activities on α-amylase. The extracts from 75%v/v and 95%v/v ethanol and GIA1 significantly delayed the glycemic absorption by lowering α-glucosidase activity and glucose transportation of SGLT1. However, the 50%v/v ethanolic extract markedly decreased the α-glucosidase activity than the SGLT1 function. Conclusion: Differences in the GIA1 contents and anti-glycemic properties of the GI leaf extract was dependent on ethanol concentrations. Furthermore, the inhibitory effects of the 75%v/v and 95%v/v ethanolic extracts on α-glucosidase and SGLT1 were relevant to GIA1 content.